Metaheuristics for Structural Design and Analysis - Toklu, Yusuf Cengiz; Bekdas, Gebrail; Nigdeli, Sinan Melih (John Wiley & Sons, Incorporated, 2021)
Metaheuristics for Structural Design and Analysis discusses general properties and types of metaheuristic techniques, basic principles of topology, shape and size optimization of structures, and applications of metaheuristic algorithms in solving structural design problems. Analysis of structures using metaheuristic algorithms is also discussed. Comparisons are made with classical methods and modern computational methods through metaheuristic algorithms. The book is designed for senior structural engineering students, graduate students, academicians and practitioners.